Genetic characterization of pediatric B-cell acute lymphoblastic leukemia in Argentina uncovers molecular heterogeneity and novel variants - Sol Ruiz, María; Sosa, Ezequiel; Avendaño, Daniel; Gomez Mercado, Ignacio; Lacreu, María Laura; Riccheri, Cecilia; Schuttenberg, Virginia; Aversa, Luis; Vazquez, Elba; Gueron, Geraldine; Cotignola, Javier (Frontiers in Pharmacology, 2025)
IntroductionAcute lymphoblastic leukemia is the most common childhood cancer, yet its diagnosis and risk classification remain incomplete in many regions due to limited access to molecular studies.MethodsWe present the first comprehensive genetic and molecular characterization of childhood B-cell Acute lymphoblastic leukemia in Argentina using whole-transcriptome sequencing of diagnostic bone marrow samples from 32 patients enrolled in the international clinical protocol ALLIC-BFM-2009.ResultsBy integrating publicly available bioinformatic tools, we achieved molecular subtyping in over 93% of cases, a significant increase from the 31% rate attained through traditional methods. Our analysis revealed a diverse landscape of known and novel genetic alterations, including gene fusions, single nucleotide variants, and gene expression signatures relevant to prognosis and therapy. Importantly, we identified novel single nucleotide variants in DUX4, CSF3R and CREBBP, and fusion transcripts.DiscussionThis study not only reports transcriptional heterogeneity in our Latin American cohort but also supports the implementation of open-source bioinformatic pipelines in resource-limited settings to enhance precision diagnosis and guide personalized treatment.